Increasing the Competitiveness of MSMEs in the Global Market by Integrating Digital Marketing and Environmental Awareness: Case Study of the Implementation of Green Environmental Awareness and Green Product Pricing and Its Impact on Green Product Purchasing - Kramadibrata, Budi Santosa; Susanto, Andi Heru (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This research aims to increase the competitiveness of MSMEs in the global market by integrating digital marketing and environmental awareness: a case study of the application of green environmental awareness and green product pricing and its impact on green product purchasing. This type of research is quantitative with a cross-sectional approach. The population in this study is all MSMEs assisted by the green-based DKI Jakarta Industry, Trade, Small and Medium Enterprises Cooperative which amounts to 284 MSMEs. The sampling technique used is cluster random sampling. Determination of the sample size using the Generic formula so that the sample obtained amounted to 164 respondents. The main research instrument used was a questionnaire with Likert Scale. The data analysis technique used is Confirmatory Factor Analysis Second Order to determine the value of each instrument factor used with standardized factor loading and t-value criteria. The accepted value in the test was more than 0.5 for standardized factor loading and more than 1.96 for t-value. Structural model analysis is carried out using Struqtural Equation Modeling (SEM). The analysis process was carried out using Lisrel with fit model criteria, namely chi square, GFI, AGFI, NFI and CFI, PNFI, and AIC.  The results of the analysis show that there is a direct influence of green marketing on green product purchasing. There is a direct influence of green environmental awareness on green product purchasing. There is a direct influence of green product pricing on green product purchasing. There is a direct influence of green marketing on green environmental awareness. There is a direct influence of green environmental awareness on green product pricing